2019
DOI: 10.1039/c8ta11300a
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing solvent effects to integrate alkylamine into metal–organic frameworks for exceptionally high CO2 uptake

Abstract: Alkylamine modified MOF prepared with a less polar solvent (cyclohexane) has a higher alkylamine loading amount and higher CO2 uptake than when prepared in a more polar solvent (dichloromethane).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 62 publications
0
39
0
Order By: Relevance
“…In recent years, the highly charged metal‐containing secondary building units (SBUs) were frequently employed to fabricate chemically stable MOFs (e.g., Zr‐MOFs and MIL series of MOFs). [ 98,99 ] Since the pioneer Férey et al first reported the Cr‐based MOF (named MIL‐101) in 2005, [ 100 ] it has been extensively studied in many fields, such as gas adsorption and separation, [ 101 ] heterogeneous catalytic, [ 102 ] and proton conduction, [ 43,44,103–106 ] which is mainly attributed to its high surface area, mesoporous feature and excellent chemical stability.…”
Section: Mofs As a Versatile Platform For Proton Conductorsmentioning
confidence: 99%
“…In recent years, the highly charged metal‐containing secondary building units (SBUs) were frequently employed to fabricate chemically stable MOFs (e.g., Zr‐MOFs and MIL series of MOFs). [ 98,99 ] Since the pioneer Férey et al first reported the Cr‐based MOF (named MIL‐101) in 2005, [ 100 ] it has been extensively studied in many fields, such as gas adsorption and separation, [ 101 ] heterogeneous catalytic, [ 102 ] and proton conduction, [ 43,44,103–106 ] which is mainly attributed to its high surface area, mesoporous feature and excellent chemical stability.…”
Section: Mofs As a Versatile Platform For Proton Conductorsmentioning
confidence: 99%
“…Less polar solvents, or even better nonpolar, are more suitable for the encapsulation of an alkylamine into MOFs, promoting the CO 2 uptakes. [94] Hence, amine functionalized MOFs, which allow chemisorption of CO 2 , appear as superior materials for practical applications.…”
Section: Mofs As Chemisorbents For Co 2 Capturementioning
confidence: 99%
“…The loading grade of the MIL‐101(Cr) was demonstrated to be related to the polarity of the solvent used for the tethering process. Less polar solvents, or even better nonpolar, are more suitable for the encapsulation of an alkylamine into MOFs, promoting the CO 2 uptakes …”
Section: Introductionmentioning
confidence: 99%
“…There are two obvious broad diffraction peaks at 1230-1450 cm −1 (D peak) and 1450-1580 cm −1 (G peak) in all samples. Serious widening of D and G peak of Raman spectra indicates the existence of many sp 2 and sp 2 -sp 3 hybridized structure in incomplete graphitized materials [38,39]. It is necessary to resolve overlapped peaks by using fitting treatment at 1300 cm −1 (D 1 peak), 1520 cm −1 (D 3 peak), 1200 cm −1 (D 4 peak), and 1550 cm −1 (G peak).…”
Section: Carbon Structure Analysis Of Samples At Different Ammonia Acmentioning
confidence: 99%
“…With the development of human society, massive emissions of CO 2 from fossil fuel combustion cause serious pollution on the environment and pose a threat to human health [1]. A post-combustion capture (PCC) technology including chemical and physical absorption methods can capture effectively CO 2 from flue gas [2], but a chemical absorption method using organic amine (such as alkanolamine and ethanolamine) now faces the dilemma of equipment corrosion, high capital cost, and solvent consumption [3]; thus, a physical absorption method using carbon-based porous materials, such as activated carbons (ACs), has been extensively explored, to remove CO 2 from flue gas, due to its advantages of being low in cost, highly efficient, and environmentally sustainable [4]. In addition, using methane as a carbon source could accurately adjust the pore size to promote CO 2 adsorption and separation.…”
Section: Introductionmentioning
confidence: 99%